Opportunities for an en-route to polymer inclusion membrane approach from conventional hydrometallurgical recycling of WPCBs: a mini-review - Jha R.; Mishra G.; Agrawal M.; Dhanunjaya Rao M.; Meshram A.; Singh K.K. (My University, 2025)
Waste printed circuit boards (WPCBs) are an essential part of any electric and electronic equipment (EEE). A plethora of valuable metals such as gold, palladium, silver, and copper along with the presence of hazardous metals like cadmium, lead and mercury is a good motivation for designing an effective recycling process for WPCBs. The pyrometallurgical route shows environmental challenges like the formation of toxic gases such as dioxins and furans. Overtaking the limitations of the pyrometallurgy route, the hydrometallurgical route comes into existence with very low capital cost, low gas generation, and an environmentally friendly process. This article reviews the conventional hydrometallurgical processes followed en route to newer polymer inclusion membrane (PIMs) routes for the treatment of WPCBs to recover trace metals. The conventional hydrometallurgical approaches such as cementation, ion exchange, and solvent extraction are efficient in recovering metals from WPCBs. However, the purity of recovered metals is also compromised by metals of lower concentrations. PIMs are found as low-cost processes for the extraction of valuable metals from WPCBs leach liquor as this process combines extraction and stripping steps. Additionally, this process is a nature-friendly, chemically stable processing route for the extraction of heavy and toxic metallic elements. © 2022 Canadian Institute of Mining, Metallurgy and Petroleum.